2013
DOI: 10.1186/1757-1146-6-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flexor tenotomy on healing and prevention of neuropathic diabetic foot ulcers on the distal end of the toe

Abstract: BackgroundFlexor tenotomy is a minimally invasive surgical alternative for the treatment of neuropathic diabetic foot ulcers on the distal end of the toe. The influence of infection on healing and time to heal after flexor tenotomy is unknown. Flexor tenotomy can also be used as a prophylactic treatment. The effectiveness as a prophylactic treatment has not been described before.MethodsA retrospective study was performed with the inclusion of all consecutive flexor tenotomies from one hospital between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(100 citation statements)
references
References 12 publications
2
95
0
3
Order By: Relevance
“…Seven retrospective case series of percutaneous digital flexor tendon tenotomies performed in patients to heal apex toe ulcers presented a recurrence rate between 0 and 20% over a mean follow‐up between 11 and 36 months in a total of 231 treated patients . Four of the seven studies also assessed effects of digital tenotomy of a toe where no ulcer was present at the time of the procedure, in a cumulative total of 58 patients with impending ulcers (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven retrospective case series of percutaneous digital flexor tendon tenotomies performed in patients to heal apex toe ulcers presented a recurrence rate between 0 and 20% over a mean follow‐up between 11 and 36 months in a total of 231 treated patients . Four of the seven studies also assessed effects of digital tenotomy of a toe where no ulcer was present at the time of the procedure, in a cumulative total of 58 patients with impending ulcers (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the seven studies also assessed effects of digital tenotomy of a toe where no ulcer was present at the time of the procedure, in a cumulative total of 58 patients with impending ulcers (i.e. abundant callus on tip of the toe or thickened nails) and presented no ulcer occurrence in a mean 11–31 months follow‐up .…”
Section: Resultsmentioning
confidence: 99%
“…While controlled studies on this topic are lacking, various studies have shown that a digital flexor tendon tenotomy may reduce the risk of a recurrent plantar foot ulcer in selected patients with initially nonhealing ulcers when compared with non‐surgical treatment for these ulcers . Flexor tenotomy may also reduce the risk of ulcer development in patients with abundant callus on the tip of their toes or thickened nails . We consider flexor tenotomy a promising procedure in a patient who has a toe ulcer, or a pre‐ulcerative sign on the toe, that fails to respond to non‐surgical treatment, and requires normalization of foot structure to prevent ulceration.…”
Section: Treating Risk Factors For Ulcerationmentioning
confidence: 99%
“…The possible benefits of digital flexor tenotomy likely outweigh the harm, as few complications have been reported . Patients who have pre‐ulcerative lesions for which they have frequent non‐surgical treatment that does not improve outcome may value and prefer treatment by flexor tenotomy.…”
Section: Treating Risk Factors For Ulcerationmentioning
confidence: 99%
“…Seven retrospective case series of percutaneous digital flexor tendon tenotomy performed in patients with the goal of healing distal toe ulcers showed in a cumulative total of 231 treated patients that 92–100% ulcers healed in a mean time to healing of 21–40 days, with a low rate of reported complications . While controlled studies on this topic are lacking, we consider this procedure to be a promising intervention in patients with hammertoes and recalcitrant toe ulcers that fail conservative treatment.…”
Section: Surgical Offloading Interventionsmentioning
confidence: 99%